Synthesis, Characterization, and Enhanced Optical and Dielectric Properties of Pure and Ni-Doped ZnO Nanoparticles for Advanced Electronic Applications - Muhammad Fawad; Nabeel Maqsood; Ahmad Nawaz; Bilal Islam; Malik Daniyal Zaheer; Kateřina Skotnicová (Results in Engineering)
Nickel (Ni)-doped zinc oxide (ZnO) nanoparticles have garnered significant attention due to their tunable structural, optical, and electronic properties, making them ideal candidates for various advanced applications. This study focuses on the synthesis, characterization, and evaluation of the electrical and electronic properties of pure and Ni-doped ZnO nanoparticles (Ni:ZnO) synthesized via a co-precipitation method with varying Ni concentrations (2%, 4%, 6%, and 8%). X-ray diffraction analysis confirmed the wurtzite hexagonal structure of ZnO, with lattice distortion increasing proportionally to Ni doping. A secondary NiO phase was detected at higher doping levels, indicating the solubility limit of Ni in ZnO. The average crystallite size, calculated using Debye-Scherrer's equation, decreased from 31 nm in pure ZnO to 23 nm in 8% Ni-doped ZnO, confirming doping-induced size reduction. UV-visible spectroscopy revealed a blue shift in the optical bandgap from 3.23 eV for pure ZnO to 3.41 eV for 8% Ni-doped ZnO, attributed to Burstein-Moss effect. Fourier transform infrared spectroscopy identified changes in vibrational modes, with shifts in peaks corresponding to Zn-O and Ni-O bonds, indicating successful Ni incorporation. Scanning electron microscopy (SEM) and energy-dispersive X-ray spectroscopy confirmed uniform particle morphology and elemental composition. Dielectric studies showed that the dielectric constant increased significantly with Ni doping, reaching a maximum value of 69 at 6% doping, while AC conductivity improved with frequency, demonstrating frequency-dependent conductivity due to hopping charge carriers. The findings reveal that Ni doping enhances the structural, optical, and dielectric properties of ZnO, making it suitable for optoelectronics, high-frequency devices, and dielectric materials.